2014
DOI: 10.1681/asn.2014030275
|View full text |Cite
|
Sign up to set email alerts
|

Race, Class, and AKI

Abstract: with Kaposi's sarcoma virus had normal EPO production under normoxic conditions and increased EPO mRNA production under hypoxic conditions, in contrast with the effects of CMV in this cell line. Further studies showed that it was the CMV-IE gene expression (identical to CMV-IE proteins detected in CMV-infected HEPCs and human kidneys with CKD) that directly mediated the lowering of the EPO mRNA. In a clinically relevant cellular study, treatment of the cells with valganciclovir, an inhibitor of CMV-late gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…However, in the non-Asian subgroup, it was 15%. African ancestry is also a risk factor for AKI [45]. In a large cohort study of hospitalized COVID-19 patients, 76.9% of the patients who were hospitalized with COVID-19 and 70.6% of those who died were Black, whereas the Black population only accounted for 31% of the total population [46].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the non-Asian subgroup, it was 15%. African ancestry is also a risk factor for AKI [45]. In a large cohort study of hospitalized COVID-19 patients, 76.9% of the patients who were hospitalized with COVID-19 and 70.6% of those who died were Black, whereas the Black population only accounted for 31% of the total population [46].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several studies have shown that alcohol abuse is strongly associated with higher cardiovascular risk [ 50 ]. This association is superimposed upon the fact that patients in most deprived areas present higher prevalence of established risk factors for AKI, such as hypertension, diabetes and obesity [ 51 ]. An observational study, including 10,588 patients, showed that black ethnicity was associated with 30% higher risk for AKI and this association remained significant after adjustment for several demographic, cardiovascular risk factors, kidney markers and time-varying number of hospitalizations (HR.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled estimated AKI incidences in the Asian subgroup was lower than Western subgroup (8% vs 28%). Black race is a risk factor for AKI 44 .…”
Section: Discussionmentioning
confidence: 99%